Analysis of Sustainable Infrastructure Development in Sorong Regency Based on Environmentally Technology Criteria - Widodo, Slamet; Murni, Murni; A. Rahman, Rian Hidayat; Ibal, La (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2024)
Sorong Regency is inhabited by around 188,6779 people in West Papua Province. At this time, Sorong Regency is starting to develop infrastructure to support economic activities in Sorong actively. It has become one of the districts focused on development in the eastern part of Indonesia, with examples of infrastructure projects including the improvement and creation of several roads, bridges, irrigation and the construction of Sorong Special Economic Zones (SES). This research aims to determine the sustainable infrastructure development of Sorong Regency, especially in the Aimas, Mariat, Mayamuk, and Salawati Districts based on environmental and technological criteria. The research method used is Multidimensional Scaling (MDS) with the Rapinfra (Rapid Appraisal of Infrastructure) method. The results of the research regarding the status of infrastructure development in the Aimas District area with an index value of 48.74% and Mariyat District with an index value of 58.92% in terms of environmental criteria are considered less sustainable. In comparison Mayamuk District with an index value of 68.56% and Salawati District with an index value of 60.00% are considered sufficient. Meanwhile, in terms of technological criteria, the Aimas District with an index value of 65.07% and the Mariyat District with an index value of 60.22% are considered not or not yet sustainable; meanwhile, the Mayamuk District area with an index value of 84.64% and the Salawati District with an index value of 91.55 are considered to be quite sustainable.